Correlation between Ferritin and Iron Overload in Heart and Liver in BetaThalassaemia Major Patients in Shahrekord, Iran - Kiavash Fekri; Nabiollah Asadpour; Majid Hamidi; Mohsen Karimian (National Journal of Laboratory Medicine, 2018)
Introduction: Beta-thalassaemia is one of the severe types of thalassaemia with very high healthcare costs. Iron overload in heart and liver is the most fatal complication in betathalassemia. Aim: This study was performed to investigate the correlation between the heart and liver overload and blood ferritin level, Nucleated Red Blood Cells (NRBCs) proportion, and other effective factors involved. Materials and Methods: In this descriptive-analytical study, 59 thalassaemia major patients were investigated. These patients underwent transfusion 2-3 times a week and were enrolled in the study by convenience, non random sampling. Iron overload in heart and liver was measured by MRI T2*. Furthermore, some variables such as haemoglobin level, transfusion intervals, transfusion rate, spleen size, the type and dose of chelators, and NRBCs as well as demographic variables including age, gender, and race were analysed in this study. The data were analysed by SPSS version 18. Results: Our study showed that if there was a reduction in NRBCs proportion, ferritin level and liver quantitative iron overload decreased (p<0.05) and heart iron overload increased (p<0.05). Also, an increment of ferritin level was correlated with an increment of iron overload in heart and liver. Less mean haemoglobin was correlated with decrease in liver iron overload and increase in heart iron overload. Conclusion: Ferritin could not be constantly used alone as a suitable index of overload in liver and heart in beta-thalassaemia major patients and it is necessary to take the specific conditions of each patient into account and to use other parameters such as haemoglobin and NRBCs proportion besides ferritin.